Editorial: let's get physical—long‐term benefits of vigorous physical activity in patients with nonalcoholic fatty liver disease. Authors' reply. Issue 6 (23rd February 2023) - Henry, Austin; Paik, James M.; Austin, Patrick; Eberly, Katherine Elizabeth; Golabi, Pegah; Younossi, Issah; Henry, Linda; Gerber, N. Lynn; Younossi, Zobair M.
LINKED CONTENT: This article is linked to Henry et al papers. To view these articles, visit https://doi.org/10.1111/apt.17308 and https://doi.org/10.1111/apt.17336